Online identity work dynamics of Instagram micro-influencers: an extreme case approach - Bergs, Yoy; Peters, Pascale; Lub, X. D.; Blomme, R. J. (Frontiers in Psychology, 2023)
Background: Advanced media technologies have become an integral part of people’s daily lives, providing them with new tools and environments for the formation and enactment of their identities. To date, the literature acknowledges that media technologies, such as social networking sites, are used to form and enact online identities, and that these platforms can simultaneously pose challenges to individuals’ identity work. However, we know little about the precise online identity work strategies that individuals employ in response to the challenges they face over time. Objective: This paper examines the online identity work dynamics of Instagram micro-influencers, for whom social network sites enable and guide them in forming and enacting their online identities on a daily basis. The study was guided by the following research question: What are the challenges that Instagram micro-influencers perceive online and what are the online identity work strategies that they employ in response to these challenges over time? Methods: This study employs an extreme case approach to rigorously explore the lives of seven micro-influencers on Instagram. We combine in-depth data from narrative interviews, longitudinal data from online autobiographical narratives revealed through the participants' Instagram timelines, and follow-up interviews. Results: Our analysis revealed three main themes that highlight the challenges that Instagram micro-influencers face online: (1) amplified social expectations, (2) feelings of inauthenticity, and, as a result thereof, (3) psychological distress. We found that these challenges were viewed as catalysts for their online identity work processes. We identified three key online identity work strategies that the Instagram micro-influencers employed in response over time: (1) experimenting with their online identities, followed by either (2) segmenting between their online and offline identities, or (3) adding identities through online multiplicity. Conclusion: Our research provides new insights into how individuals may respond to the challenge of managing their online identities over time by engaging in different online identity work strategies. This study highlights the importance of designing online media technologies that enable individuals to cope with online challenges. We emphasize the need to design online spaces for (1) the expression of authentic identities, (2) community building, and (3) online multiplicity.